2012
DOI: 10.12741/ebrasilis.v5i2.204
|View full text |Cite
|
Sign up to set email alerts
|

Riqueza de borboletas (Lepidoptera) em um fragmento urbano de Cerrado em Mato Grosso do Sul, Brasil

Abstract: Resumo. Borboletas estão entre os artrópodes melhor estudados, pois participam de diversas interações ecológicas. Apesar de já existirem muitos inventários de borboletas publicados no Brasil, nenhuma informação ainda existe em Mato Grosso do Sul. O presente estudo teve como objetivo avaliar a riqueza de espécies de borboletas encontradas em um remanescente urbano de cerrado em Campo Grande, Centro-Oeste do Brasil, além de indicar a presença de espécies raras e indicadora de ambiente preservado. Foram registrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
9
1
3
Order By: Relevance
“…According to the Jackknife 1 estimator, 72.3% of the species pool was sampled at Serra de São José, higher compared to the 66-68% found by Pereira et al (2017) in Serra do Cipó and by Silva et al (2015) in a Special Protection Area of Nova Lima (Minas Gerais), respectively. Bogiani et al (2012) found 81% of the species estimated by Jackknife 1 in a Cerrado urban area, although only 60 species were recorded using the same two sampling methods and a very similar effort-hour to our study. The species richness estimated for Serra de São José indicates that the area, although smaller, might surpass the butterfly biodiversity of other campos rupestres areas.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…According to the Jackknife 1 estimator, 72.3% of the species pool was sampled at Serra de São José, higher compared to the 66-68% found by Pereira et al (2017) in Serra do Cipó and by Silva et al (2015) in a Special Protection Area of Nova Lima (Minas Gerais), respectively. Bogiani et al (2012) found 81% of the species estimated by Jackknife 1 in a Cerrado urban area, although only 60 species were recorded using the same two sampling methods and a very similar effort-hour to our study. The species richness estimated for Serra de São José indicates that the area, although smaller, might surpass the butterfly biodiversity of other campos rupestres areas.…”
Section: Discussionsupporting
confidence: 63%
“…The richness of butterfly species on Serra de São José is within the expected range for the campos rupestres, although it is higher than that observed in other inventories for the Brazilian Cerrado and open grassy vegetation (e.g., Bogiani et al 2012, Araújo & Paprocki 2015, Martins et al 2017. For example, Nery et al…”
Section: Discussionmentioning
confidence: 62%
“…However, compared with records for several Brazilian states such as recorded by Isehard and Romanowski (2004), Marchiori and Romanowski (2006), Emery et al (2006), Dessuy and Morais (2007), Pinheiro et al (2008), Isehard et al (2010), Ritter et al (2011), Zacca and Bravo (2012), and Bogiani et al (2012), the number of species found is lower. This fact could very well be explained by the sampled area size and sampling effort (Table 4).…”
Section: Discussioncontrasting
confidence: 57%
“…Eurema albula and Eurema elathea , also registered in this site, have cosmopolitan habits and great adaptations for disturbed areas (Isehard et al 2007, Bogiani et al 2012). It is important to mention that Morpho helenor , which was well sampled – 51 individuals (Table 1), disappears quickly when severe disturbances and size reduction of forests occur (Santana 2005).…”
Section: Discussionmentioning
confidence: 74%
“…São estimadas cerca de 10 mil espécies para o bioma (BROWN; GIFFORD, 2002;DINIZ et al, 2013). O conhecimento dessa diversidade é resultado principalmente de estudos com adultos como, por exemplo, listas de espécies e revisões taxonômicas (EMERY et al, 2006;FERRO;DINIZ, 2007;BOGIANI et al, 2012;SCHERRER et al, 2013). Sendo assim, há relativamente poucos estudos sobre os estágios imaturos dos Lepidoptera do Cerrado (e. g. MUNIZ et al, 2012;BÄCHTOLD et al, 2013;DINIZ et al, 2013;BRAGA;DINIZ, 2015).…”
Section: Introdução Geralunclassified